Evaluation of microalgae as quorum-sensing inhibitors to protect gnotobiotic Aartemia franciscana (Kellogg, 1906) against Vibrio campbellii - Abdul Halim, Nurul Aini (2020)
Diseases remain as one of the major constraints in aquaculture industry. The use of microalgae as quorum sensing inhibitor (QSI) to disrupt communication in pathogenic bacteria could be another disease control alternative as regulation of virulence factors in bacterial pathogens are regulated by quorum sensing (QS). Thus, the present study evaluated different microalgae isolated from shrimp pond as quorum sensing inhibitors in in vitro and in in vivo settings. In this study, the effects of nine microalgae species on acyl-homoserine lactone-regulated phenotypes of two QS reporter strains (Chromabacterium violaceum CV026 and Escherichia coli JB523) and anti-Acute Hepatopancretic Necrosis Disease (anti-AHPND) were investigated. Five microalgae pellet extracts; Picochlorum eucaryotum, Monoraphidium sp., Amphora coffeiformis, Desertifilum tharense and Bulboplastis apyrenoidosa inhibited violacein production of quorum sensing reporter strain CV026 with the largest inhibition zone of P. eucaryotum (6.85 ± 0.15 mm). Further tests showed that the supernatant of algae extracts also inhibited quorum sensing using the QS reporter strain JB523. In JB523 reporter strain, a significant decrease in QS-regulated GFP production (p < 0.05) were observed in all microalgae species except for Spirulina platensis. The highest percentage of inhibition of JB523 were demonstrated by P. eucaryotum (1 ± 0.02 %) respectively, Monoraphidium sp. (1 ± 0.04 %) and Chlorella sp. (1 ± 0.02 %). The growth of all reporter strains was found to be unaffected by the microalgal samples. The most promising micro-algal strains as bacterial disease control agents were found to be P. eucaryotum, A. coffeiformis and D. tharense. Meanwhile, screening of anti- AHPND activities revealed that three green algae P. eucaryotum, Monoraphidium sp. and Chlorella sp. were able to inhibit two AHPND strains of Vibrio parahaemolyticus. The best three microalgae species with QSI activities; A. coffeiformis, D. tharense and P. eucaryotum were selected for Artemia challenge assay. A significant (p < 0.05) survival were observed in Artemia bioencapsulated with A. coffeiformis (95 ± 0 %), D. tharense (85 ± 10 %), and P. eucaryotum (60 ± 0 %) even after challenged with Vibrio campbellii, BB120 (12.5 ± 5 %). The results in this study indicated that quorum quenching microalgae has the potential to be used as biocontrol tool to manage disease outbreak particularly vibriosis in aquaculture farms.